Anomalous inflation of a nematic balloon. (September 2020) - He, Qiguang; Zheng, Yue; Wang, Zhijian; He, Xuming; Cai, Shengqiang
Abstract: Inflation of an elastomer balloon is one of the most classical and important problems in the field of nonlinear elasticity. Many intriguing phenomena associated with the inflation of elastomer balloons such as snap-through instability and bulge propagation have been often observed and intensively studied. In this article, we report a new phenomenon during the inflation of a cylindrical balloon made from nematic elastomer. We found in the experiment that with a small increment of inflating pressure, the balloon contracts significantly along its axial direction while expands in its radial direction. With further increase of the pressure, the balloon expands mainly in the radial direction while maintains its length almost unchanged. Finally, the balloon expands both in the radial and axial directions abruptly with a tiny increase of inflating pressure, often leading to rupture of the balloon. The inflation behavior of the nematic balloon can be changed when it is subjected to an additional axial load. To quantitatively understand the experiments, we adopt a quasi-convex free energy function of nematic elastomer to derive the relationship between the inflating pressure and its deformation state. We have shown that the anomalous inflation of the nematic balloon is closely associated with the soft elasticity of the nematic elastomer. Our theoretical predictions agree with experimental measurements well with only two material parameters separately determined by uniaxial tension test of nematic elastomer.